2013
DOI: 10.1111/1751-7915.12075
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of recombinant Escherichia coli cells co‐expressing poly‐γ‐glutamic acid (γ‐PGA) synthetase and glutamate racemase for differential yielding of γ‐PGA

Abstract: Poly-γ-glutamic acid (γ-PGA) is a promising environmental-friendly material with outstanding water solubility, biocompatibility and degradability. However, it is tough to determine the relationship between functional synthetic enzyme and the strains' yield or substrate dependency. We cloned γ-PGA synthetase genes pgsBCA and glutamate racemase gene racE from both L-glutamate-dependent γ-PGA-producing Bacillus licheniformis NK-03 and L-glutamate-independent B. amyloliquefaciens LL3 strains. The deduced RacE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Bacillus amyloliquefaciens LL3 is a glutamic acid‐independent γ‐PGA‐producing strain, which suggests that the intracellular glutamate is the only substrate for γ‐PGA synthesis (Cao et al ., ). We previously reported that the deletion of RocR, a transcriptional regulator of glutamate metabolism, may have contributed to the increase of γ‐PGA production in B. amyloliquefaciens LL3 (Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Bacillus amyloliquefaciens LL3 is a glutamic acid‐independent γ‐PGA‐producing strain, which suggests that the intracellular glutamate is the only substrate for γ‐PGA synthesis (Cao et al ., ). We previously reported that the deletion of RocR, a transcriptional regulator of glutamate metabolism, may have contributed to the increase of γ‐PGA production in B. amyloliquefaciens LL3 (Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Metabolic evolution had been successfully used to enhance the production of many fermentation products, such as succinate (Jantama et al ., ; Zhu et al ., ), l ‐lactate (Grabar et al ., ), D‐lactate (Zhou et al ., ), ethanol (Yomano et al ., ) and l ‐alanine (Zhang et al ., ). Since γ‐PGA synthesis was relevant to cell growth of B. amyloliquefaciens (Cao et al ., ), metabolic evolution was performed in the strain NK‐A9 to improve cell growth and γ‐PGA production. After the 10th time transfer, growth of the recombinant strain had been much better than that of NK‐A9 and NK‐A7 (Figs S6A and B).…”
Section: Resultsmentioning
confidence: 99%
“…B. amyloliquefaciens was engineered to enhance γ-PGA production by heterologous expression of the Vitreoscilla gene (vgd) encoding hemoglobin to overcome the low concentration of dissolved oxygen [67,88]. In contrast, Chao et al developed a γ-PGA-producing E. coli strain by heterologous expression of γ-PGA synthetase and glutamate racemase from B. licheniformis or B. amyloliquefaciens [89]. The tri-peptide glutathione, which is the most abundant antioxidant, thiol-containing compound among organisms [100], is produced enzymatically and by microbial fermentation.…”
Section: Peptidesmentioning
confidence: 99%
“…For industrial applications, most studies have relied on biosynthesizing PGA in B. subtilis (Ashiuchi, 2013;Halmschlag et al, 2019;Park et al, 2005;Wang et al, 2017) and other Bacillus species (Feng et al, 2017(Feng et al, , 2015Ogunleye et al, 2015;Tian et al, 2014;Xavier et al, 2019;Yoon et al, 2000), although there have been significant efforts in moving the complex to recombinant hosts such as E. coli (Ashiuchi et al, 1999;Cao et al, 2013Cao et al, , 2011Jiang et al, 2006;Liu et al, 2019;Wang et al, 2011), Corynebacterium glutamicum (Xu et al, 2019), and even tobacco plants (Tarui et al, 2005). A major advantage of recombinant hosts is that PGA synthesis can be decoupled from native cellular regulatory processes and engineered for higher productivity, yield, stereochemical composition, and molecular weight.…”
Section: Introductionmentioning
confidence: 99%